Antibiotic use in pig farms at different levels of intensification - Farmers’ practices in northeastern Thailand - Hallenberg, Gunilla S.; Jiwakanon, J.; Angkititrakul, S.; Kang-air, S.; Osbjer, K.; Lunha, K.; Sunde, M.; Järhult, J.D.; Boeckel, Thomas P. van; Rich, Karl M.; Magnusson, Ulf (Public Library of Science, 2020)
Understanding the patterns and drivers of antibiotic use in livestock is crucial for tailoring efficient incentives for responsible use of antibiotics. Here we compared routines for antibiotic use between pig farms of two different levels of intensification in Khon Kaen province in Thailand. Among the 113 family-owned small-scale farms (up to 50 sows) interviewed did 76% get advice from the pharmacy about how to use the antibiotics and 84% used it primarily for treating disease. Among the 51 medium-scale-farms (100–500 sows) belonging to two companies did 100% get advice about antibiotic use from the company’s veterinarian (P<0.0001) and 94% used antibiotics mostly as disease preventive measure (P<0.0001). In 2 small scale farms 3rd generation cephalosporins, tylosin or colistin were used; antibiotics belonging to the group of highest priority critically important antimicrobials for human medicine. Enrofloxacin, belonging to the same group of antimicrobials, was used in 33% of the small-scale and 41% of the medium-scale farms. In the latter farms, the companies supplied 3–4 antibiotics belonging to different classes and those were the only antibiotics used in the farms. The median and mean estimated expenditure on antibiotics per sow was 4.8 USD (IQR = 5.8) for small-scale farms and 7 USD and 3.4 USD for the medium-scale farms belonging to the two respective companies. Our observations suggest to target the following areas when pig farming transitions from small-scale to medium-scale: (i) strengthening access to professional animal health services for all farmers, (ii) review of the competence and role of veterinary pharmacies in selling antibiotics and (iii) adjustment of farming company animal health protocols towards more medically rational use of antibiotics.